Fiscal Equalization, Tax Salience, and Tax Competition - Martin Altemeyer-Bartscher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper analyzes the efficiency consequences of local revenue policies if jurisdictions try to attenuate the pressures of inter-regional competition for mobile factors by substituting attention-grabbing tax instruments that spotlight an additional tax burden with rather inconspicuous ones. We show that the substitution of tax instruments with the view to reduce the perceived tax price may suppress the under-exploitation of tax bases that typically goes along with fiscal equalization.
Keywords: H77; H22; H30; 330